THE ROLE OF THE ANTI CORRUPTION COMMISSION (CAC) IN DRIVING BUREAUCRATIC REFORM TOWARDS GOOD GOVERNANCE IN TIMOR LESTE - Jaimito Soares, Patricia Baliana da Costa, Carolina da Cruz Simeão Fatima Martins, Domingos Loe Soar (FKIP UMN ALWASHLIYAH, 2026)
Corruption is a primary obstacle to development and bureaucratic reform in post-conflict nations like Timor-Leste, where state institutions are still consolidating. In an environment characterized by a weak rule of law and strong patronage networks inherited from its period of struggle for independence, corruption not only harms state finances but also erodes government legitimacy and hinders human resource development. This study aims to critically and comprehensively analyze the role of the Anti-Corruption Commission (Comissão Anti-Corrupção/CAC) in promoting bureaucratic reform towards good governance in Timor-Leste. Utilizing a qualitative research method with a case study approach, data were collected through a comprehensive analysis of documents, including CAC annual reports, statistical data from the World Bank and Transparency International, national legal frameworks, and relevant literature. The findings indicate that the CAC plays a crucial and multifaceted role through its